Prioritering, styring og likebehandling. Utfordringer i norsk helsetjeneste - Sinding Aasen, Henriette; Magnussen, Anne-Mette; Bærøe, Kristine; Bringedal, Berit (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Prioritization is a necessity in healthcare, in the allocation of limited resources. Which criteria and considerations prove decisive, however, when it comes to prioritization in practice? The dominant political objective of the Norwegian public healthcare system is to provide services of high quality, fairly distributed among Norway's citizens. Regulatory and economic policies, professional values, administrative organization and distribution of resources are among the factors that influence everyday decision-making and the realization of healthcare objectives. How do healthcare providers experience these factors? Which hidden prioritization mechanisms are at play? How are equal treatment and fair distribution of services understood in practice? These are among the questions discussed in the various chapters of the book, written by scholars in social science, law, philosophy and medicine. While researchers, academics, students and healthcare providers are the targeted readers, this book will be of interest to everyone engaged in today´s challenges related to healthcare prioritization, including decision-makers at various political and administrative levels. This anthology is the result of the research project Prioritizing Health Care - Tensions and Interplay between Legal, Political, Economic and Professional Perspectives, funded by the Norwegian Research Council."